Correlation of knowledge and attitude of pregnant women towards their oral health practice - Azizah, Mutiara Nuraini; Ramadhani, Mochamad Nur; Suwargiani, Anne Agustina; Susilawati, Sri (Universitas Padjadjaran, 2021)
Introduction: During pregnancy, hormonal changes can increase susceptibility to oral diseases. Oral disease can pose a risk for the baby's oral health and pregnancy outcomes. Oral problems and their complications during pregnancy can be prevented by maintaining oral health behaviours that include knowledge, attitude, and practice. This study was aimed to analyse the correlation of knowledge and attitude pregnant women toward their oral health practice. Methods: An analytic research with a cross-sectional method was conducted towards 65 pregnant women at Sukajadi Community Health Centre (Puskesmas), Bandung, taken as a sample through purposive sampling technique. Data collection was carried out using a questionnaire. The statistical test used in this study was the Spearman correlation test. Results: The study showed that 66.2% of pregnant women had good knowledge of oral health care, 27.7% had adequate knowledge, and 6.2% had poor knowledge. Oral health care attitude found that 56.9% of pregnant women had a good attitude, 43.1% had a fair attitude, and none were in the poor category. Oral health care practice of pregnant women resulted from 15.4% was in a good category, 60.0% in the fair category and 24.6% was in the poor category. The statistical analysis results between the attitude and the practice of oral health care showed a weak correlation with the correlation coefficient (rs) 0.124 and a significance value (p-value) was higher than 0.05 (0.325), indicating that there was no significant relationship between attitudes and the practice of oral health care. Conclusion: There is weak correlation between knowledge and attitude of pregnant women toward their oral health practice.